2020
DOI: 10.1002/jts.22585
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Class Analysis of Mental Health Beliefs Related to Military Sexual Trauma

Abstract: Military veterans with histories of military sexual trauma (MST) are at risk for several negative mental health outcomes and report perceived barriers to treatment engagement. To inform interventions to promote gender‐sensitive access to MST‐related care, we conducted an exploratory, multiple‐group latent class analysis of negative beliefs about MST‐related care. Participants were U.S. veterans (N = 1,185) who screened positive for MST within the last 2 months and reported a perceived need for MST‐related trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…An affirmative response to either question results in a positive screen. The current study is an extension of Hahn et al, 12 a cross-sectional study that identified latent classes of mental health beliefs among a subsample of 1,185 Veterans who endorsed perceived need for MST-related mental health care by an affirmative response to the survey item: "In the past year, did you ever want or need help with any emotional or mental health concerns related to any military sexual trauma experience?" We linked those survey data with VHA administrative data in order to examine associations with outpatient MST-related care in the year following MST detection.…”
Section: Design and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…An affirmative response to either question results in a positive screen. The current study is an extension of Hahn et al, 12 a cross-sectional study that identified latent classes of mental health beliefs among a subsample of 1,185 Veterans who endorsed perceived need for MST-related mental health care by an affirmative response to the survey item: "In the past year, did you ever want or need help with any emotional or mental health concerns related to any military sexual trauma experience?" We linked those survey data with VHA administrative data in order to examine associations with outpatient MST-related care in the year following MST detection.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Instructions for these items were specifically focused on MST-related care. We examined the latent classes of mental health beliefs as constructed by Hahn et al 12 Using a multiple-group (with gender as the grouping variable) LCA, Hahn et al 12 identified four mutually exclusive groups of treatment belief classes: low barrier class (32.4%); stigma-related beliefs class (34.1%); negative perceptions of care class (10.1%); and high barrier class (23.5%). Model fit indices indicated that the four-class solution was the superior fit; sample size adjusted Bayesian information criteria = 5,219.66 and entropy = .78.…”
Section: Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations